Are the roots of human economic systems shared with non-human primates?. (February 2020) - Addessi, Elsa; Beran, Michael J.; Bourgeois-Gironde, Sacha; Brosnan, Sarah F.; Leca, Jean-Baptiste
Highlights: We review work in experimental economics, field primatology and neuroscience to assess the extent of economic abilities in non-human primates. We argue in favour of evolutionary precursors of complex human economic abilities present among non-human primates. Some of the symbolic activities performed by non-human primates show the capacity to barter and even proto-monetary behavior. We spell our definitional criteria for what can count as economic behaviour beyond mere application of economic models to animal behaviour. Abstract: We review and analyze evidence for an evolutionary rooting of human economic behaviors and organization in non-human primates. Rather than focusing on the direct application of economic models that a priori account for animal decision behavior, we adopt an inductive definition of economic behavior in terms of the contribution of individual cognitive capacities to the provision of resources within an exchange structure. We spell out to what extent non-human primates' individual and strategic decision behaviors are shared with humans. We focus on the ability to trade, through barter or token-mediated exchanges, as a landmark of an economic system among members of the same species. It is an open question why only humans have reached a high level of economic sophistication. While primates have many of the necessary cognitive abilities (symbolic and computational) in isolation, one plausible issue we identify is the limits in exerting cognitive control to combine several sources of information. The difference between human and non-human primates' economies might well then be in degree rather than kind.